Factors Affecting Back Pain in Pregnant Women in the Third Trimester Literature Review - Murbiah, Murbiah; Panduragan, Santhna Letchmi; Pardi, Kasmahwati; Hassan, Hafizah Che; Husin, Husin (International Journal of Health Sciences, 2025)
Introduction: Back pain is caused by pain in the lumbosacral area. The increase in intensity with increasing gestational age results from a shift in the center of gravity and changes in body posture. Back pain from sacroiliac/lumbar can be a long term back pain if not treated efficiently. Material and Methods: Literature review aims to examine more deeply about back pain in pregnant women in the third trimester, there were factors that influenced it by reviewing. Methods literature review by searching on Google Scholar and PubMed. The keyword criteria are "pregnancy", "back pain", "low back pain pregnancy factors", "back pain pregnant women activities". After the study was conducted, national articles 9 and 15 were obtained. Results: Factors that affect back pain in third trimester pregnant women can be classified from gestational age, age, parity, daily activities that affect back pain and body relaxation can reduce back pain.. Conclusion: Review that has been conducted, it was found that the factors that influence back pain in pregnant women in the third trimester can be classified according to gestational age, age, parity, daily activities .